2011
DOI: 10.2478/v10143-011-0031-4
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Wi-Fi Based Indoor Positioning Accuracy

Abstract: An Analysis of Wi-Fi Based Indoor Positioning AccuracyThe increasing demand for location based services inside buildings has made indoor positioning a significant research topic. This study deals with indoor positioning using the Wireless Ethernet IEEE 802.11 (Wireless Fidelity, Wi-Fi) standard that has a distinct advantage of low cost over other indoor wireless technologies. The aim of this study is to examine several aspects of location fingerprinting based indoor positioning that affect positioning accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 5 publications
1
45
0
Order By: Relevance
“…The results showed that this parameter has rather high fluctuations and is quite difficult to assess. One of the areas of research that utilizes the evaluation of signal strength at the input of receiver is the widely used identification methods for the estimation of device positioning in the network coverage area [5][6][7]. The main informative parameter in these studies is also the RSSI parameter while the attenuation in free space and additional beacons to reduce the fluctuations of signal are applied in order to assess location of the devices.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The results showed that this parameter has rather high fluctuations and is quite difficult to assess. One of the areas of research that utilizes the evaluation of signal strength at the input of receiver is the widely used identification methods for the estimation of device positioning in the network coverage area [5][6][7]. The main informative parameter in these studies is also the RSSI parameter while the attenuation in free space and additional beacons to reduce the fluctuations of signal are applied in order to assess location of the devices.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…A set of particles is defined as a set of hypotheses of the robot position and orientation denoted at time t as S r (t) = (x [1] r (t), x [2] r (t), · · · , x [M] r (t)) , where [M] is the number of particles. First, it updates the particles representing the position and orientation of the robot by using the motion model, which is given by Eq.…”
Section: Positioning Algorithmmentioning
confidence: 99%
“…Although the hardware required to support WiFi [1,2] and Bluetooth [3,4] is easily integrated into mobile devices, both WiFi-and Bluetooth-based positioning systems are easily disturbed because interference by other signals affects their accuracy. Ultrasonic [5,6] and LRF [7,8] positioning systems have the advantage of high positioning accuracy and a relatively simple system structure.…”
Section: Introductionmentioning
confidence: 99%
“…A common indoor positioning strategy uses the pattern of the received signal strengths (RSS) of available Wi-Fi access points (APs) to calculate the current position of a Wi-Fi receiver. The strategies are able to achieve an accuracy under 10 m (Jekabsons, 2011;Zandbergen, 2009). For Wi-Fi fingerprinting which was introduced in Bahl and Padmanabhan (2000) a raster of positions is defined, where reference RSS values for each position are recorded in a trainings phase.…”
Section: Operational Principle Of the Intelligent Checkpoint (Icp) Comentioning
confidence: 99%